Measuring young people's citizenship activity. Issue 2 (1st June 2017) - Krzywosz-Rynkiewicz, Beata; Zalewska, Anna M.
In this article we present a different approach to citizenship research and understanding, with a focus on the citizenship model described by Zalewska and Krzywosz-Rynkiewicz in a study included in this thematic issue of CTL. The model developed by Zalewska and Krzywosz-Rynkiewicz consists of eight types of citizenship behaviour defined in three dimensions: (1) passive citizenship (including national identity and patriotism); (2) semi-active citizenship (civic virtues and loyalty); and (3) active citizenship (political, social, personal and change-oriented activity). A 34-question Citizenship Behavior Questionnaire (CBQ) was used to evaluate students' citizenship behaviours on a scale of 1 (strongly disagree) to 4 (strongly agree). Research was conducted in fourteen European countries with a total sample of 4920 students aged 11–12 (early adolescence, 1526 students), 14–15 (middle adolescence, 1675 students) and 17–18 (late adolescence, 1719 students), consisting of 2502 girls and 2418 boys living in cities (2300) and towns (2620). Details of the research procedure and research team and comparison between countries are also presented.